Effects of high-intensity inspiratory muscle training in rugby players - Nunes Júnior, Adauto de Oliveira; Donzeli, Marina Andrade; Shimano, Suraya Gomes Novais; de Oliveira, Nuno Miguel Lopes [UNESP]; Ruas, Gualberto; Bertoncello, Dernival (FapUNIFESP (SciELO), 2018)
Introduction: Rugby is a sport characterized by high and low intensity motor action. Therefore, the respiratory muscles need adequate work to maintain sustained effective breathing. Objective: To analyze the effects of high-intensity inspiratory muscle training (IMT) in amateur rugby players from the city of Uberaba, Minas Gerais, Brazil. Methods: This is a clinical study in which 20 amateur players underwent a pulmonary function test, respiratory muscle strength and physical capacity assessment. The participants were divided into two groups: 10 volunteers in the IMT group (G1) and 10 in the control group (G2). All the assessments were carried out before and after 12 weeks of IMT. Results: No significant changes were observed in the pulmonary function test. However, maximal voluntary ventilation, maximal inspiratory pressure, maximal expiratory pressure and distance increased significantly after IMT. Conclusion: IMT had beneficial effects on amateur rugby players. Level of evidence I; Therapeutic studies - Investigation of treatment results.
Efectos del entrenamiento de alta intensidad de la musculatura inspiratoria en atletas de rugby
Efeitos do treinamento de alta intensidade da musculatura inspiratória nos atletas de rugby
Keywords: Athletes; Physical endurance; Resistance training; Rugby